2022
DOI: 10.1039/d2ra05535j
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the preparation of high-performance inorganic mixed-halide perovskite solar cells

Abstract: This review gives a full-scale and in-depth summary of mixed halide CsPbX3 perovskite materials for the photovoltaic application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 151 publications
0
6
0
Order By: Relevance
“…In recent years, lead halide perovskite materials with the structure ABX 3 (where A is caesium, B is a lead cation and X is a halide anion) exhibit numerous advantages such as high brightness, and high photoluminescence quantum yield (PLQY) with narrow size distribution, which can provide great potential in optoelectronic devices [1]. These lead halide perovskite-based various applications such as solar cells [2][3][4][5][6][7][8][9], photodetectors [10], light-emitting diodes (LEDs) [11][12][13][14][15][16][17] and low-threshold lasers [18][19][20], etc., have been increasingly investigated. Although they have excellent optical properties, the lead halide perovskite materials' sensitive surface chemistry with moisture, oxygen in the ambient environment, and organic polar solvents are still one of the major issues.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, lead halide perovskite materials with the structure ABX 3 (where A is caesium, B is a lead cation and X is a halide anion) exhibit numerous advantages such as high brightness, and high photoluminescence quantum yield (PLQY) with narrow size distribution, which can provide great potential in optoelectronic devices [1]. These lead halide perovskite-based various applications such as solar cells [2][3][4][5][6][7][8][9], photodetectors [10], light-emitting diodes (LEDs) [11][12][13][14][15][16][17] and low-threshold lasers [18][19][20], etc., have been increasingly investigated. Although they have excellent optical properties, the lead halide perovskite materials' sensitive surface chemistry with moisture, oxygen in the ambient environment, and organic polar solvents are still one of the major issues.…”
Section: Introductionmentioning
confidence: 99%
“…All-inorganic cesium lead halide (CsPbX 3 , X = I, Br) perovskites have attracted much attention because of their superior thermal stability over their organic–inorganic hybrid counterparts, according to both experimental and theoretical results. Among the CsPbX 3 perovskite materials, the mixed halide CsPbI 2 Br is considered the most promising light absorber due to the trade-off between stability and efficiency. CsPbI 2 Br has excellent thermal/light soaking stability and a suitable band gap of ≈1.90 eV, which exhibits promising application potential in the front cell of tandem solar cells. , In recent years, the performance of CsPbI 2 Br perovskite solar cells (PSCs) has been rapidly improved through some innovations, such as modulating the crystallization process, optimizing composition, , and modifying the interface. , Yang et al reported a low-dimensional intermediate-assisted growth (LDIAG) method to control both nucleation and growth kinetics by introducing imidazole halide (IMX: IMI and IMBr) into the precursor solution .…”
Section: Introductionmentioning
confidence: 99%
“…The superior stability of all-inorganic CsPbX 3 perovskite materials compared to organic-inorganic hybrid halide perovskites is attributed to the sensitivity of organic molecules (such as MA + ) to light, heat, moisture, and irradiation, which decompose or damage the structure, limiting its application in storage, fabrication, and equipment manipulation processes [43][44][45]. The choice of synthesis technique likewise has an impact on the stability of the material.…”
Section: Introductionmentioning
confidence: 99%